'Reframing' the Bhāgavata: Preservation and Reuse in South Asian Illustrated Manuscripts. (24th September 2018) - Poddar, Neeraja
Abstract: In what is probably the earliest illustrated Bhāgavata attributed to Mewar, the Sanskrit text of the Bhāgavata, the text of a Sanskrit commentary on the Bhāgavata (by Śrīdhara Svāmin), vernacular captions, and illustrations come together to recount the adventures of Kṛṣṇa. All four elements typically occur on the recto and verso of every folio of this double-sided manuscript, creating a singular combination of text and image rarely seen in other illustrated Bhāgavatas. Close examination of the folios reveals that the borders were added subsequently; the vernacular captions are occasionally written on these attached borders, suggesting that they too were included later. This article imagines how the manuscript was handled, viewed, and used. Borders and other physical additions help ensure the manuscript's longevity while new folio numbers reorder the series. The vernacular captions were written while looking at the illustrations, referencing painted details not mentioned in the Sanskrit text; they were probably incorporated due to a shift in the manuscript's function. By paying attention to such organisational, narrative, and material aspects, this article attempts to understand how the manuscript was reframed during the course of its life.